Functional connectivity of the striatum in schizophrenia and psychotic bipolar disorder - Karcher, Nicole R. (Biol Psychiatry Cogn Neurosci Neuroimaging, 2019)
BACKGROUND: The striatum is abnormal in schizophrenia, and possibly represents a common neurobiological mechanism underlying psychotic disorders. Resting-state fMRI (RS-fMRI) studies have not reached a consensus regarding striatal dysconnectivity in schizophrenia, although these studies generally find impaired fronto-parietal and salience network connectivity. The goal of the current study was to clarify the pattern of cortico-striatal connectivity, including whether cortico-striatal dysconnectivity is transdiagnostic and extends into psychotic bipolar disorder. METHODS: We examined cortico-striatal functional connectivity in 60 healthy subjects and 117 individuals with psychosis, including 77 with a schizophrenia spectrum illness and 40 with psychotic bipolar disorder. We conducted both a cortical seed-based region-of-interest (ROI) analysis with follow-up voxel-wise analysis for any significant results. Further, a striatum seed-based analysis was conducted to examine group differences in connectivity between the striatum and the whole cortex. RESULTS: Cortical ROI analysis indicated that overall connectivity of the salience network with the striatum was reduced in psychotic disorders, which follow-up voxel-wise analysis localized to the left putamen. Striatum seed-based analyses showed reduced ventral rostral putamen connectivity with the salience network portion of the medial PFC in both schizophrenia and psychotic bipolar disorders. CONCLUSIONS: The current study found evidence of transdiagnostic cortico-striatal dysconnectivity in both schizophrenia and psychotic bipolar disorder, including reduced salience network connectivity, as well as reduced connectivity between the putamen and the medial PFC. Overall, the current study points to the relative importance of salience network hypo-connectivity in psychotic disorders.